Bringing traits back into the equation: A roadmap to understand species redistribution - Lise Comte; Romain Bertrand; Sarah Diamond; Lesley T. Lancaster; Malin L. Pinsky; Brett R. Scheffers; J. Alex Baecher; R. M. W. J. Bandara; I‐Ching Chen; Jake A. Lawlor; Nikki A. Moore; Brunno F. Oliveira; et al. (Global Change Biology, 2024)
Ecological and evolutionary theories have proposed that species traits should be important in mediating species responses to contemporary climate change; yet, empirical evidence has so far provided mixed evidence for the role of behavioral, life history, or ecological characteristics in facilitating or hindering species range shifts. As such, the utility of trait‐based approaches to predict species redistribution under climate change has been called into question. We develop the perspective, supported by evidence, that trait variation, if used carefully can have high potential utility, but that past analyses have in many cases failed to identify an explanatory value for traits by not fully embracing the complexity of species range shifts. First, we discuss the relevant theory linking species traits to range shift processes at the leading (expansion) and trailing (contraction) edges of species distributions and highlight the need to clarify the mechanistic basis of trait‐based approaches. Second, we provide a brief overview of range shift–trait studies and identify new opportunities for trait integration that consider range‐specific processes and intraspecific variability. Third, we explore the circumstances under which environmental and biotic context dependencies are likely to affect our ability to identify the contribution of species traits to range shift processes. Finally, we propose that revealing the role of traits in shaping species redistribution may likely require accounting for methodological variation arising from the range shift estimation process as well as addressing existing functional, geographical, and phylogenetic biases. We provide a series of considerations for more effectively integrating traits as well as extrinsic and methodological factors into species redistribution research. Together, these analytical approaches promise stronger mechanistic and predictive understanding that can help society mitigate and adapt to the effects of climate change on biodiversity.